2022
DOI: 10.53730/ijhs.v6ns4.6049
|View full text |Cite
|
Sign up to set email alerts
|

Role of optical coherence tomography angiography in early detection of retinal microvascular changes in adolescents with type 1 diabetes

Abstract: Purpose: Early detection of diabetic retinopathy can prevent progressive visual loss. Evaluate the role of Optical Coherence Tomography Angiography (OCTA) in early detection of diabetic retinopathy (DR) in type 1 diabetes (T1D) adolescents with normal fundus photography. Methods: Cross-sectional study included 150 eyes of 75 T1D adolescents from the Diabetes Endocrine and Metabolism Pediatric Unit, Children hospital, Cairo University. Their ages ranged from 10-18 years and diabetes duration 2 years or more. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…This variation in prevalence may be due to differences in the Body Mass Index (BMI) and the different genetic variation of populations. A study by Ahmad et al reported that 21% diabetic subjects had raised serum cholesterol i.e., >200mg/dl while 34.2% diabetic subjects of the study had raised TGs i.e., >150mg/dl [13]. While our study found out that TGs mean and SD of 197.29±68.56* for Group I (Diabetics) and 141.16±42.63 for Group II (Controls) with a MD of 56.13.…”
Section: Discussioncontrasting
confidence: 56%
“…This variation in prevalence may be due to differences in the Body Mass Index (BMI) and the different genetic variation of populations. A study by Ahmad et al reported that 21% diabetic subjects had raised serum cholesterol i.e., >200mg/dl while 34.2% diabetic subjects of the study had raised TGs i.e., >150mg/dl [13]. While our study found out that TGs mean and SD of 197.29±68.56* for Group I (Diabetics) and 141.16±42.63 for Group II (Controls) with a MD of 56.13.…”
Section: Discussioncontrasting
confidence: 56%